1994
DOI: 10.3109/00498259409043223
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic fate of14C-camostat mesylate in man, rat and dog after intravenous administration

Abstract: 1. The metabolic fate of N,N-dimethylcarbamoylmethyl 4-(4-guanidino[14C]benzoyloxy)phenylacetate methanesulphonate (14C-camostat mesylate) was investigated after i.v. administration to man (12-h infusion), and to rat and dog (bolus injection). 2. Renal excretion (mainly in 24 h) accounted for at least 80% dose in all three species, and the only two important metabolites were identified as 4-(4-guanidinobenzoyloxy)phenylacetic acid (GBPA) and 4-guanidinobenzoic acid (GBA). 3. Parent drug was not detected in hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 8 publications
3
55
0
Order By: Relevance
“…4 ¢ -CMGB isv ery instable in plasmaa nd the determination of the parentdrugisimpossible. But the metabolite,P HBA-Me,isv ery stable in plasma.Since4 ¢ -CMGB wasconverted toPHBA-Mecompletelyand quantitatively,the plasmaconcentration of PHBA-Mewasdetermined in thiss tudy.Similarr esults havebeen found in other4 ¢ -guanidinobenzoatecompoundslike nafamostat [12]and camostat [13][14][15].Inan in vivo study,the ester sitewhichconjugatesp-guanidinobenzoica cid and the otherpart wasfound ast he reaction centerasw ell as the sitef orcatabolicc hanges.Afteradministration,the parentdrugwasnotdetected in humano ranimalp lasmaowing torapid hydrolysisof the side-chain ester group,onlyt he metabolitesw eref ound. The metabolismm ayoccur byaid of the esterenzymesw hichd istributed extensivelyin animalblood and tissues.…”
Section: Discussionsupporting
confidence: 80%
“…4 ¢ -CMGB isv ery instable in plasmaa nd the determination of the parentdrugisimpossible. But the metabolite,P HBA-Me,isv ery stable in plasma.Since4 ¢ -CMGB wasconverted toPHBA-Mecompletelyand quantitatively,the plasmaconcentration of PHBA-Mewasdetermined in thiss tudy.Similarr esults havebeen found in other4 ¢ -guanidinobenzoatecompoundslike nafamostat [12]and camostat [13][14][15].Inan in vivo study,the ester sitewhichconjugatesp-guanidinobenzoica cid and the otherpart wasfound ast he reaction centerasw ell as the sitef orcatabolicc hanges.Afteradministration,the parentdrugwasnotdetected in humano ranimalp lasmaowing torapid hydrolysisof the side-chain ester group,onlyt he metabolitesw eref ound. The metabolismm ayoccur byaid of the esterenzymesw hichd istributed extensivelyin animalblood and tissues.…”
Section: Discussionsupporting
confidence: 80%
“…6C). Thus, camostat mesylate is rapidly converted into GBPA under standard cell culture conditions, but the conversion is slower than what is observed in humans (20).…”
Section: Rapid Conversion Of Camostat Mesylate To Gbpa In Cell Culturementioning
confidence: 79%
“…Expression analyses suggest that they may. TMPRSS13 activated SARS-2-S with similar efficiency as TMPRSS2 and In animal and humans camostat mesylate is rapidly hydrolyzed into the active metabolite 4-(4-guanidinobenzoyloxy) phenylacetic acid (GBPA), which is further hydrolyzed to 4guanidinobenzoic acid (GBA) (18)(19)(20). GBPA was known to retain protease inhibitor activity (34,48) but it was unclear whether GBPA would block TMPRSS2 activity with the same efficiency as camostat mesylate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another promising TMPRSS2 inhibitor candidate for COVID-19 treatment is the broad range protease inhibitor camostat. Camostat mesylate is a phenyl-4-guanidinobenzoate derivative originally developed under the name FOY-305 for the treatment of pancreatitis (Tanaka et al, 1979; Midgley et al, 1994) and has been shown to efficiently inhibit replication of different CoV in cell culture and experimentally infected mice (Kawase et al, 2012; Shirato et al, 2013; Zhou et al, 2015). Recently, Hoffmann et al showed that pretreatment of human Caco-2 colon cells and human airway cells with camostat mesylate markedly reduced entry of SARS-CoV-2 as well as VSV pseudotypes containing the SARS-CoV-2 S protein (Hoffmann et al, 2020).…”
Section: Discussionmentioning
confidence: 99%